2008
DOI: 10.1093/aje/kwn338
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Telomere Dynamics: Longitudinal Findings Among Young Adults in the Bogalusa Heart Study

Abstract: Leukocyte telomere length (LTL) is ostensibly a biomarker of human aging. Cross-sectional analyses have found that LTL is relatively short in a host of aging-related diseases. These studies have also provided indirect estimates of age-dependent LTL shortening. In this paper, the authors report findings of the first comprehensive longitudinal study of 450 whites and 185 African Americans in Louisiana (aged 31.4 and 37.4 years at baseline (1995–1996) and follow-up (2001–2006) examinations, respectively) particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
221
6
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(260 citation statements)
references
References 42 publications
31
221
6
2
Order By: Relevance
“…In line with this reasoning, CLL cases with the longest telomeres at diagnosis showed the most pronounced yearly telomere loss. It is noteworthy that similar data showing base line dependent TL alterations by time have been shown in normal blood cells indicating similar mechanisms for telomere maintenance in leukemic and normal cells [16][17][18].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In line with this reasoning, CLL cases with the longest telomeres at diagnosis showed the most pronounced yearly telomere loss. It is noteworthy that similar data showing base line dependent TL alterations by time have been shown in normal blood cells indicating similar mechanisms for telomere maintenance in leukemic and normal cells [16][17][18].…”
Section: Introductionsupporting
confidence: 75%
“…In line with this reasoning, CLL cases with the longest telomeres at diagnosis showed the most pronounced yearly telomere loss. It is noteworthy that similar data showing base line dependent TL alterations by time have been shown in normal blood cells indicating similar mechanisms for telomere maintenance in leukemic and normal cells [16][17][18].Finally, we assessed TL and clonal evolution defined by the acquisition of new copy number aberrations (CNAs) in 47 cases of which 11 were previously found to display clonal evolution [19]. These cases were mainly IGHV unmutated (64% vs. 31% for cases without clonal evolution) and had distinctly shorter TL at diagnosis (average 1,791 U vs. 2,770 U, P 5 0.052).…”
supporting
confidence: 75%
“…Some studies have shown that minorities have longer telomere length, although they suggest quicker shortening in minorities. 14,15 Another study demonstrated that blacks and Hispanics had shorter telomeres than whites. 16 One possible reason for these differences could be a differential impact of adiposity on telomere length by race, similar to the differential impact of adiposity on mortality that has been previously demonstrated between Whites and Blacks.…”
mentioning
confidence: 99%
“…While cross-sectional studies are abundant, there have been very few longitudinal studies of telomere length [Aviv et al, 2009;Ehrlenbach et al, 2009;Epel et al, 2009;Nordfjall et al, 2009;Farzaneh-Far et al, 2010]. One consistent finding from the published longitudinal data is that the rate of telomere length change over time is inversely related to the baseline telomere length [Aviv et al, 2009;Farzaneh-Far et al, 2010].…”
Section: Future Directionsmentioning
confidence: 99%